Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/ecc.13722
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to adjuvant endocrine therapy among White British and ethnic minority breast cancer survivors in the United Kingdom

Abstract: Objective Around half of women do not take adjuvant endocrine therapy (AET) as prescribed. Research suggests that adherence rates vary across ethnic groups. This study compared AET adherences rates in White British women and women from minority ethnic groups in the United Kingdom. Methods This is an observational study with 2001 breast cancer survivors recruited from outpatient clinics. Eligible women were diagnosed with primary breast cancer and prescribed AET within the last 3 years. Adherence was measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…In accordance with heretofore literature (16,29,37,53), a significant proportion of study participants (44.4 %) did not adhere to their prescribed medication regimen among which approximately two-thirds were pertaining to unintentional and one-third to intentional non-adherers. Moreover, our study revealed that non-adherers, specifically intentional non-adherers, had lower beliefs in the necessity of AET and exhibited higher levels of concern towards it, a finding corroborated by previous research (28,29,32).…”
Section: Beliefs About Medicines and Their Association With Demograph...supporting
confidence: 85%
See 3 more Smart Citations
“…In accordance with heretofore literature (16,29,37,53), a significant proportion of study participants (44.4 %) did not adhere to their prescribed medication regimen among which approximately two-thirds were pertaining to unintentional and one-third to intentional non-adherers. Moreover, our study revealed that non-adherers, specifically intentional non-adherers, had lower beliefs in the necessity of AET and exhibited higher levels of concern towards it, a finding corroborated by previous research (28,29,32).…”
Section: Beliefs About Medicines and Their Association With Demograph...supporting
confidence: 85%
“…Potential reasons for this finding could be attributed to the brevity of the scale, consisting of only 4 to 5 items, and deviation from a normal distribution (40). However, a decrease in Cronbach's alpha due to these factors does not necessarily indicate a lack of reliability in the scale, as previously reported in the literature (16).…”
Section: Table I Sociodemographic and Clinical Data Of All Participat...mentioning
confidence: 50%
See 2 more Smart Citations
“…Taking Europeans as the reference geographical group, MA was the highest at 6 months for Asians, but it fell significantly below that of Europeans for all ethnicities at 12 months. It is known that many factors affect MA, including belonging to an ethnic minority,27 28 and having cultural beliefs about medications,29 with even differences between migrants and refugees 30. However, we favour the hypothesis that comparable personal, social and economic determinants are important in our patients independently from their ethnicity and that their interplay is responsible for similar patterns of MA.…”
Section: Discussionmentioning
confidence: 59%